A Burial Mound in the Town of Cimişlia in Southern Part of the Republic of Moldova: Relative and Absolute Chronology of the Burials - Popovici, S.; Kaiser, E. (Археологія і давня історія України, 2021)
The grave mound 8 the in city of Cimişlia, Republic Moldova is located on the first terrace of the Cogâlnic River. Burials from the Eneolithic to the Sarmatian period, a ditch and cult structure have been discovered in it. The relative and absolute dating of the burial series of the Eneolithic — Early Bronze Age is being clarified.